2023
DOI: 10.3389/fbioe.2023.1189726
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modeling of hepatocellular carcinoma niche on decellularized tomato thorny leaves: a novel natural three-dimensional (3D) scaffold for liver cancer therapeutics

Abstract: Liver cancer is now one of the main causes leading to death worldwide. To achieve reliable therapeutic effects, it is crucial to develop efficient approaches to test novel anticancer drugs. Considering the significant contribution of tumor microenvironment to cell’s response to medications, in vitro 3D bioinspiration of cancer cell niches can be regarded as an advanced strategy to improve the accuracy and reliability of the drug-based treatment. In this regard, decellularized plant tissues can perform as suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…A recent study reported the preparation of a new cellulosic 3D scaffold based on decellularized tomato thorny leaves which was recellularized with human hepatocellular carcinoma cancer cells (HepG2 cells) to mimic the tumor microenvironment for chemotherapeutic testing of prilocaine, an anticancer drug, on hepatocellular carcinoma [169]. This vegetal scaffold is an ideal candidate for liver cancer modeling.…”
Section: Applications Of Decellularized Plants In Drug Testingmentioning
confidence: 99%
“…A recent study reported the preparation of a new cellulosic 3D scaffold based on decellularized tomato thorny leaves which was recellularized with human hepatocellular carcinoma cancer cells (HepG2 cells) to mimic the tumor microenvironment for chemotherapeutic testing of prilocaine, an anticancer drug, on hepatocellular carcinoma [169]. This vegetal scaffold is an ideal candidate for liver cancer modeling.…”
Section: Applications Of Decellularized Plants In Drug Testingmentioning
confidence: 99%
“…Esmaeili et al [24] decellularized the Alstroemeria flower stem and modified it with chitosan to fabricate a new scaffold for soft and hard tissue engineering. Very recently, Ahmadian et al [25] developed a novel 3D natural scaffold from decellularized tomato thorny leaves and used it as an ideal candidate for in vitro 3D hepatocellular carcinoma modeling.…”
Section: Characterization Of Decellularized Scaffoldsmentioning
confidence: 99%
“…Recently, 3D scaffolds have emerged as an important tool for 3D in vitro tumor models and drug administration in cancer treatment. The in vitro model of a tumor has been used as an instrument for research into drug toxicity, the development of drugs, and anti‐cancer processes in addition to cancer cell biological processes, which include cancer growth, cell invasion, and metastasis‐related cancer cell movement 10,11 . 3D scaffolds are frequently used as drug‐releasing implants for in vivo cancer therapy and localized medication administration 12 …”
Section: Introductionmentioning
confidence: 99%